Berberis aristata combined with Silybum marianum on lipid profile in patients not tolerating statins at high doses. Issue 1 (March 2015) - Derosa, Giuseppe; Romano, Davide; D'Angelo, Angela; Maffioli, Pamela
Abstract: Aim: To evaluate the effects of Berberis aristata combined with Silybum marianum in dyslipidemic patients intolerant to statins at high doses. Methods: 137 euglycemic, dyslipidemic subjects, with previous adverse events to statins at high doses, were enrolled. Statins were stopped for 1 month (run-in), then they were re-introduced at the half of the previously taken dose. At randomization, patients tolerating the half dose of statin, were assigned to add placebo or B. aristata / S. marianum 588/105 mg, 1 tablet during the lunch and 1 tablet during the dinner, for six months. We evaluated lipid profile and safety parameters variation at randomization, and after 3, and 6 months. Results: B. aristata / S. marianum reduced fasting plasma glucose (−9 mg/dl), insulin (−0.7 μU/ml), and HOMA-index (−0.35) levels compared to baseline and also to placebo. Lipid profile did not significantly change after 6 months since the reduction of statin dosage and the introduction of B. aristata / S. marianum, while it worsened in the placebo group both compared to placebo and with active treatment (+23.4 mg/dl for total cholesterol,  +19.6 mg/dl for LDL-cholesterol,  +23.1 mg/dl for triglycerides with placebo compared to B. aristata / S. marianum ). We did not record any variations of safety parameters in nether of groups. Conclusions: B. aristata / S. marianum can be considered as addition to statins in patients not tolerating high dose of these drugs. Highlights: Adverse events are more common at higher doses of statins, and often contribute to patients low adherence to treatment. To reduce the risk of statin-induced adverse events, we can use a lower dose of statin combined with nonstatin drugs. Berberis aristata / Silybum marianum reduced fasting plasma glucose, insulin and HOMA-index compared to baseline and also to placebo. Lipid profile did not change with statin at half dose and B. aristata / S. marianum, while it worsened with placebo. B. aristata / S. marianum can be used in addition to statins in patients not tolerating high dose of these drugs.